RETRACTED: The Arabidopsis Malectin-Like Leucine-Rich Repeat Receptor-Like Kinase IOS1 Associates with the Pattern Recognition Receptors FLS2 and EFR and Is Critical for Priming of Pattern-Triggered Immunity . Issue 7 (28th July 2014) - Chen, Ching-Wei; Panzeri, Dario; Yeh, Yu-Hung; Kadota, Yasuhiro; Huang, Pin-Yao; Tao, Chia-Nan; Roux, Milena; Chien, Shiao-Chiao; Chin, Tzu-Chuan; Chu, Po-Wei; Zipfel, Cyril; Zimmerli, Laurent
Abstract : This work describes the function of the RLK IOS1 in Arabidopsis immunity against bacteria. IOS1 is required for optimal function of the immune receptors FLS2 and EFR and β-aminobutyric acid-induced resistance and priming. IOS1 associates with FLS2, EFR, and BAK1 and controls the ligand-induced FLS2-BAK1 association. Abstract: Plasma membrane-localized pattern recognition receptors such as FLAGELLIN SENSING2 (FLS2) and EF-TU RECEPTOR (EFR) recognize microbe-associated molecular patterns (MAMPs ) to activate the first layer of plant immunity termed pattern-triggered immunity (PTI ). A reverse genetics approach with genes responsive to the priming agent β-aminobutyric acid (BABA ) revealed IMPAIRED OOMYCETE SUSCEPTIBILITY1 (IOS1) as a critical PTI player. Arabidopsis thaliana ios1 mutants were hypersusceptible to Pseudomonas syringae bacteria. Accordingly, ios1 mutants demonstrated defective PTI responses, notably delayed upregulation of PTI marker genes, lower callose deposition, and mitogen-activated protein kinase activities upon bacterial infection or MAMP treatment. Moreover, Arabidopsis lines overexpressing IOS1 were more resistant to P. syringae and demonstrated a primed PTI response. In vitro pull-down, bimolecular fluorescence complementation, coimmunoprecipitation, and mass spectrometry analyses supported the existence of complexes between the membrane-localized IOS1 and FLS2 and EFR. IOS1 also associated with BRASSINOSTEROID INSENSITIVE1-ASSOCIATED KINASE1 (BAK1) in a ligand-independent manner and positively regulated FLS2/BAK1 complex formation upon MAMP treatment. Finally, ios1 mutants were defective in BABA -induced resistance and priming. This work reveals IOS1 as a regulatory protein of FLS2- and EFR-mediated signaling that primes PTI activation upon bacterial elicitation.